Myrcia excelsa (Myrtaceae), a new species from Espírito Santo, Brazil - Gaem, Paulo Henrique; Fernandes, Thiago; Valdemarin, Karinne Sampaio; Lucas, Eve; Mazine, Fiorella Fernanda (Phytotaxa, 2021)
Myrcia De Candolle (1827: 401) (Myrciinae, Myrteae, Myrtaceae) is represented by 101 species in the Brazilian state of Espírito Santo (Santos et al. 2020). In addition, a new endemic species is here proposed based on a unique combination of morphological features. Morphological terminology follows Radford et al. (1974) and Lucas et al. (2018). A conservation assessment is proposed according to the IUCN (2012). For this, geographic coordinates of collections were estimated from specimen labels when missing and geographical parameters were calculated using GeoCAT (Bachman et al. 2011).